Public Procurement Reform in Morocco - Lipson, Rachel; Benouniche, Salim; Keita, Abdoulaye; Faridi, Khadija (World Bank, Washington, DC, 2014)
Over the last decade Morocco has made important strides in responding to citizen demands for more transparency, accountability, and shared prosperity. This has also extended into the public sector and its varied functions. In Morocco public contracts account for some 17 percent of GDP and are responsible for critical activities in the economy, including delivery of key public services.2 Given its important role, the Government of Morocco (GoM) prioritized public procurement for comprehensive reforms. Starting with 2003 Country Procurement Assessment Report (CPAR) Morocco embarked on a productive dialogue with the World Bank to improve its procurement system and optimize the performance of its public investments.